Multilevel Analysis of Socioeconomic and Cultural Factors on Chronic Energy Deficiency among Pregnant Women in Madura - Ratna Indriyani; Bhisma Murti; Novita Ana Anggraini; Yenny Puspitasari (Journal Of Nursing Practice, 2026)
Background: Chronic Energy Deficiency (CED) is one of the health problems that often occurs in pregnant women in various countries, especially in regions with low economic levels and vulnerable communities. Purpose: The purpose of this study is to examine the influence of socioeconomic and cultural contextual factors on the occurrence of CED in pregnant women. Methods: The research design is explanatory research with a cross-sectional approach. The research sample consists of 200 pregnant women with CED and 200 pregnant women without CED in Madura. The dependent variable in this study is the incidence of CED, while the independent variables are regional conditions, access to health services, parity, food availability, and CED preventive behavior. Data analysis in the study is univariate and linear regression with a multilevel approach using SPSS 23. The research ethics certificate 001867/EC/KEPK/I/II/2024. Results: Level 1 is rural and urban areas, access to health services, parity, food availability, and preventive behavior for CED. Level 2 is the subdistrict level. Subdistrict conditions have a contextual influence on the variation in the occurrence of CED in pregnant women, namely significant values in rural and urban areas (p=0.009), significant values in access to health services (p=0.013), significant values for parity (p=0.022), significant values for food availability (p=0.049), and significant values for CED preventive behavior (p=0.029). Conclusion: The highest prevalence of CED was found in coastal areas, followed by villages, and the lowest in cities. Women with low parity (primiparas) are not entirely free from the risk of CED. Conversely, pregnant women in urban areas tend to have better access to health facilities, nutritional information, and a variety of foods, resulting in a relatively lower risk of CED.